Emotion Recognition Performance in Children with Callous Unemotional Traits is Modulated by Co-occurring Autistic Traits. Issue 6 (2nd November 2021) - Bedford, Rachael; Carter Leno, Virginia; Wright, Nicola; Bluett-Duncan, Matthew; Smith, Tim J.; Anzures, Gizelle; Pickles, Andrew; Sharp, Helen; Hill, Jonathan
ABSTRACT: Objective: Atypical emotion recognition (ER) is characteristic of children with high callous unemotional (CU) traits. The current study aims to 1) replicate studies showing ER difficulties for static faces in relation to high CU-traits; 2) test whether ER difficulties remain when more naturalistic dynamic stimuli are used; 3) test whether ER performance for dynamic stimuli is moderated by eye-gaze direction and 4) assess the impact of co-occurring autistic traits on the association between CU and ER. Methods: Participants were 292 (152 male) 7-year-olds from the Wirral Child Health and Development Study (WCHADS). Children completed a static and dynamic ER eye-tracking task, and accuracy, reaction time and attention to the eyes were recorded. Results: Higher parent-reported CU-traits were significantly associated with reduced ER for static expressions, with lower accuracy for angry and happy faces. No association was found for dynamic expressions. However, parent-reported autistic traits were associated with ER difficulties for both static and dynamic expressions, and after controlling for autistic traits, the association between CU-traits and ER for static expressions became non-significant. CU-traits and looking to the eyes were not associated in either paradigm. Conclusion: The finding that CU-traits and ER are associated for static but not naturalistic dynamic expressions may be because motion cues in the dynamic stimuli draw attention to emotion-relevant features such as eyes and mouth. Further, results suggest that ER difficulties in CU-traits may be due, in part, to co-occurring autistic traits. Future developmental studies are required to tease apart pathways toward the apparently overlapping cognitive phenotype.